Dissecting pathophysiology of a human dominantly inherited disease, familial amyloidotic polyneuropathy, by using genetically engineered mice - Li Zhenghua; Yamamura Kenichi (Frigid Zone Medicine, 2022)
Familial amyloidotic polyneuropathy (FAP) is a type of systemic amyloidosis characterized by peripheral and autonomic neuropathy. Although FAP is a typical autosomal dominant disorder caused by a point mutation in the TTR gene, the average age at onset varies significantly among different countries. This discrepancy clearly suggests that a combination of intrinsic factors as well as extrinsic (environmental) factors shapes the development of FAP. However, these factors are difficult to analyze in humans, because detailed pathologic tissue analysis is only possible at autopsy. Thus, mouse models have been produced and used to disentangle these factors. This review covers the mouse models produced thus far and how these models are applied to analyze intrinsic and extrinsic factors involved in disease development and to test drug efficacy.